Transport Characteristics of Tailing Sand Particles under Slotted Tube Overlapped with Geotextile and Steel Mesh. (16th January 2023) - Yang, Chun-bo; Wang, Lin-bing; Wang, Yuan; Li, Qing-wen; Huang, Jing-qi
Abstract : Compared with a one-dimensional test, a two-dimensional test has the potential to study the transport characteristics of particles in tailings under different filtration materials. Due to the different test conditions and the complex test environment, the existing devices generally have limited measuring range or high accuracy. Thus, it is urgent to develop an advanced device to improve the ability of the transport characteristics of particles. In this study, a two-dimensional radial flow device is designed for analyzing the transport characteristics of particles which combine the water tank with adjustable pressure and the seepage body providing a tailing sand environment. An experimental system is built, and a seepage process is carried out to explore the transport characteristics of particles. The results indicate that when head difference remains stable, the mixture consisting of the tailing sand and water gradually transports to the vicinity of the slotted tube along the diameter direction. With an increase in head difference, the tailing sand particle size in the mixture shows a slow upward trend, which migrates in the tailing sand. And the proportion of tailing sand particles with different sizes varies under different head differences. Separation of the mixture consisting of tailing sand particles and water occurs near infiltration material, while the mixture has different transportation laws under different filtration materials. Under geotextile, most fine tailing sand particles which transport from the edge remain in geotextiles, causing an increase in the proportion of fine particles around the slotted tube. However, most fine particles pass through steel mesh, leading to a decrease in the proportion of fine particles.